Рецензия; Электричество; № 8 - Воробьев А. А. Александр Акимович; Воробьёв Н. И.; Трескина М. Н.; Воробьёв Г. А.; Каляцкий И. И.; Трубицин А. М.; Дмитриевский В. С.; Калганов А. Ф.; Кучин В. Д. (1954, 1954)
Рец. на кн.: Техника высоких напряжений. Ч.1-2 / Под общ. ред. Л. И. Сиротинского.-М.-Л., 1951-1953.